Raising Learner Satisfaction in Online Computer Programming and Information Technology Courses: One Instructor's Five Successful Strategies - Ryan Rucker (Flexible Learning Association of New Zealand, 2023)
Online learning has continued to rise in popularity among learners, educators, and university administrators over the last three decades.  However, one of the biggest challenges for educators is adapting to best practices, pedagogies, tools, and technologies when delivering instruction in this environment. Remembering that learners have a choice when enrolling in a university degree program, it is critical that educators focus on learner satisfaction.  Many universities are concentrated on retention and recruitment and having a high learner satisfaction rate can improve these two areas.  When an educator finds a strategy that helps improve learner satisfaction, it is critical that they share this knowledge with other professionals.  This case study highlights five strategies that worked within computer programming and information technology courses to help improve learner satisfaction.  These strategies consisted of providing individualized video feedback, using simulation products, integrating real-world projects, offering conversations with industry experts, and providing prompt learner engagement.